Research on the Push-pull Forward Capacitor Clamp Zero-voltage Synchronous Rectifier Converter - LIU Guowang; ZHANG Yuchi; WANG Lin (Kongzhi Yu Xinxi Jishu)
In order to improve the efficiency of the push-pull converter, a clamp capacitor is connected in series between the center tap of the high voltage side of the primary side of the traditional push-pull circuit, so that the leakage energy can be absorbed without damage and returned to the input side. The coupling relationship between the two windings of the primary side is established to make the two windings of the primary side transfer energy to the secondary side at the same time, so as to reduce the loss of the absorption circuit of the primary side. At the same time, the synchronous rectifier diode is replaced by the synchronous rectifier tube at the output side by the double guiding pass characteristic of synchronous rectifier MOS tube at the output side, so as to reduce the power loss of the rectifier circuit. A double closed-loop control strategy is proposed for the weak current control part. Finally, a 240 W engineering prototype is built based on modeling analysis and simulation, and the key waveform of the control loop and main power devices are analyzed. The analysis results show that compared with the traditional push-pull converter, the circuit topology can effectively reduce the switching loss of the bridge arm and the power loss of the secondary side rectifier circuit, and the overall efficiency of the converter is improved by about 3%.